Pengaruh Model Problem Based Learning Terhadap Berpikir Kritis Siswa Dalam Pembelajaran Matematika Kelas 4 SDN 1 Sidamulya - Wahyuni, Novia Sri; Kusumah, Rita (Universitas Muhammadiyah Magelang, 2024)
This research aims to determine students' critical thinking abilities after applying the problem based learning model to mathematics learning with equivalent fraction material. This research uses an experimental method with a one group pretest posttest design. The sample used in this research was 21 class IV students at SDN 1 Sidamulya. The instrument used in this research was a written test in the form of essay questions. Sampling was carried out using a saturated sampling technique, namely a sampling technique when members of the population are used as samples. The data analysis technique used is the Paired Sample Test, which previously tested the prerequisites, namely normality and homogeneity. The results of this research show that the results of the Paired Sample Test of critical thinking skills were obtained by students before and after using the problem based learning model with Sig. of 0.000. Where 0.001 < 0.05 then ?? is rejected and ?? is accepted, meaning that there is a difference in students' critical thinking abilities in learning mathematics using the PBL model for class IV students at SDN 1 Sidamulya. So, it can be concluded that in this research the Problem Based Learning (PBL) model has an influence on students' critical thinking abilities in learning mathematics.